2022
DOI: 10.3389/fpsyg.2022.957582
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of transcranial pulsed current stimulation on relieving athlete’s mental fatigue

Abstract: ObjectiveTo explore the effect of independently developed transcranial pulsed current stimulation (tPCS) on alleviating athlete’s mental fatigue.MethodsA total of 60 college athletes were randomly divided into the active stimulation group (current intensity:1.5 mA, lasting for 15 min) and the sham stimulation group. Subjective questionnaires, behavior test, and functional near-infrared spectroscopy (fNIRS) test were conducted before and after the experiment. Two-way ANOVA with repeated measures was used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Physiological and cognitive‐behavioral outcomes. Three studies indicated significant effects of tPCS on biochemical (Wu et al., 2022a), mental (Shen et al., 2022), and physical fatigue (Wu et al., 2022b). Although one study demonstrated that tPCS over the somatosensory cortex improves sensory perception (Saito et al., 2019), another study failed to show any effects over the posterior parietal lobe on tactile discrimination (Saito et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Physiological and cognitive‐behavioral outcomes. Three studies indicated significant effects of tPCS on biochemical (Wu et al., 2022a), mental (Shen et al., 2022), and physical fatigue (Wu et al., 2022b). Although one study demonstrated that tPCS over the somatosensory cortex improves sensory perception (Saito et al., 2019), another study failed to show any effects over the posterior parietal lobe on tactile discrimination (Saito et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size in studies on healthy male and female populations ranged from 5 to 100 individuals between the ages of 18 and 65 (Alon et al., 2011; Dissanayaka, Farrell, et al., 2022; Dissanayaka, Zoghi, et al., 2022; Dissanayaka, Zoghi, Farrell, et al., 2020; Dissanayaka, Zoghi, Hill, et al., 2020; Jaberzadeh et al., 2014, 2015; Luu et al., 2016; Morales‐Quezada et al., 2016; Morales‐Quezada, Castro‐Saavedra, et al., 2015; Morales‐Quezada, Cosmo, et al., 2015; Paneri et al., 2016; Vasquez et al., 2016). Since women's menstrual cycle may potentially affect the size of CSE induced by tPCS, some studies have exclusively recruited male participants 21–25 years old (Saito et al., 2019, 2022) or college athletes (Shen et al., 2022; Wu et al., 2022a, 2022b). In studies with patient populations, the sample sizes ranged from 6 to 70 participants between the ages of 2 and 85 (Alon et al., 2011; Barra et al., 2022; Castro et al., 2021; Iddings et al., 2019, 2021; Liu et al., 2021; Singh et al., 2019; Thibaut, Russo, Hurtado‐Puerto, et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations